Employer Training Needs in Hawaii: Summary Report - Stephen A. Woodbury (W.E. Upjohn Institute for Employment Research, 1992)
The Survey of Employer Training Needs in Hawaii was undertaken to gather information and data on the needs and preferences of employers in Hawaii regarding government assistance with training. The need for such information was created by passage of Act 68, Session Laws of Hawaii 1991, which created the Hawaii Employment and Training Fund "to assist employers and workers through innovative programs to include, but not be limited to, business-specific training, upgrade training, new occupational skills, management skills, and support services to improve the long-term employability of Hawaii's people."
Keywords: J0; J4; 330; employer; employee; job; training; Hawaii; Woodbury